2019
DOI: 10.3390/antibiotics8010026
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profiling and Comparison of Human and Animal Methicillin-Resistant Staphylococcus aureus (MRSA) Isolates from Serbia

Abstract: The aim of this study was to characterize a collection of methicillin-resistant Staphylococcus aureus (MRSA) isolates of human and animal origin from Serbia. In total, 36 MRSA isolates—30 obtained from humans and six from companion animals—were investigated by PCR for the presence of antibiotic and biocide resistance determinants and virulence genes (PVL—Panton–Valentine leukocidin, ETs—exfoliative toxins, TSST—toxic shock syndrome toxin, SEs—staphylococcal enterotoxins, and MSCRAMMs—microbial surface componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 73 publications
1
27
1
Order By: Relevance
“…Our results demonstrate that S. aureus isolates from human specimens were multi-resistant to antibiotics and produce more biofilm than the isolates collected from animal-derived samples. The high percentage (78.6%) of the human-derived isolates with multiple antibiotic resistance is in accordance with a recent study carried out in Serbia [12]. On the other hand, in other studies the animal-derived isolates showed a higher biofilm production than human-derived isolates [13].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results demonstrate that S. aureus isolates from human specimens were multi-resistant to antibiotics and produce more biofilm than the isolates collected from animal-derived samples. The high percentage (78.6%) of the human-derived isolates with multiple antibiotic resistance is in accordance with a recent study carried out in Serbia [12]. On the other hand, in other studies the animal-derived isolates showed a higher biofilm production than human-derived isolates [13].…”
Section: Discussionsupporting
confidence: 89%
“…In our previous study, only a single animal-derived isolate and four human-derived isolates derived from a severe poisoning case showed the simultaneous presence of seg and sei [6]. In another recent study, sei was the second most diffuse enterotoxin in humans [12]. In addition, the animal strains showed the simultaneous presence of sea and see at 14.3%, according to another study on enterotoxin-producing S. aureus isolated from mastitic cows [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This clone disappeared and was replaced by the southern German clone (MRSA-ST228-I) and the New York/Japan epidemic clone (MRSA-ST5-II) between 2001 and 2004 [142]. Recent studies reported the local predominance of this clone in many countries including European countries [143,144], the Middle East, Asia, and South America [145]. Another epidemic clone, MRSA-ST22, has been predominately identified in recent years throughout the Middle East [44,45,[146][147][148][149][150][151][152][153][154], Europe [155][156][157][158][159][160], and Asia [161][162][163].…”
Section: Discussionmentioning
confidence: 99%
“…SCC mec type III was the most predominant SCC mec type followed by type IV. Type III was also the most frequent SCC mec type in studies in Iran [ 32 , 33 ], Serbia [ 34 ], Brazil [ 35 ] and Europe [ 36 ]. The most prevalent spa type in our study was t037.…”
Section: Discussionmentioning
confidence: 99%